Integrated analysis of ARHGAP6 potential function and prognostic value in acute myeloid leukemia - Debin Yang; Yuanzhe Li; Ping Ma; Fankai Xiao (PLoS ONE, 2025)
Background Leukemia recurrence continues to be the primary cause of treatment failure, it is meaningful to find new biomarkers for its treatment. In this study, we aim to use cell line study to assess the expression and prognostic value of ARHGAP6 in acute myeloid leukemia. Methods We applied two acute myeloid leukemia cell lines in the research. Expression level, proliferation assay and apoptosis assay for ARHGAP6 in those cell lines were involved for the study. Then, GEO, TCGA data and bioinformatics analysis were evaluated. Results THP-1 and U937 cell lines both had higher expression levels of ARHGAP6 than control. The cell proliferation of THP-1 and U937 transfected with ARHGAP6 siRNA was significantly reduced. Knock down the gene ARHGAP6 increases AML cell apoptosis. The overall survival (OS) and disease-free survival (DFS) was assessed against the expression of ARHGAP 6 using the KM plotter databases. High expression ARHGAP6 was associated poor OS and DFS in AML. Enrichment analysis suggested that ARHGAP6 mainly mediated the function of growth factor binding, immunoglobulin binding, mRNA binding. Involved in LCK proto-oncogene, Src family tyrosine kinase, tyrosine kinase non receptor 2, platelet derived growth factor receptor beta and Rho associated coiled-coil containing protein kinase 1. Conclusion From cell lines-based functional assays to bioinformatic analysis, this study demonstrated that clinical potential of ARHGAP6 as a novel biomarker of AML.